Fifty years later: Emerging functions of IgE antibodies in host defense, immune regulation, and allergic diseases - Oettgen, Hans C. (Journal of allergy and clinical immunology, 2016)
Fifty years ago, after a long search, IgE emerged as the circulating factor responsible for triggering allergic reactions. Its extremely low concentration in plasma created significant hurdles for scientists working to reveal its identity. We now know that IgE levels are invariably increased in patients affected by atopic conditions and that IgE provides the critical link between the antigen recognition role of the adaptive immune system and the effector functions of mast cells and basophils at mucosal and cutaneous sites of environmental exposure. This review discusses the established mechanisms of action of IgE in pathologic immediate hypersensitivity, as well as its multifaceted roles in protective immunity, control of mast cell homeostasis, and its more recently revealed immunomodulatory functions.